Detection of coconuts location using separability filter and Hough Transform - Haniza, Yazid; Mohamed Rizon, Mohamed Juhari; Sugisaka, Masanori; Puteh, Saad; Ali Yeon, Md Shakaff; Abdul Rahman, Mohd. Saad (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 14th - 15th May 2005 at Putra Palace Hotel, Kangar, Perlis.